Neoadjuvant paclitaxel/olaparib in comparison to paclitaxel/carboplatin in patients with HER2-negative breast cancer and HRD: long-term survival of the GeparOLA study - Fasching, Peter Andreas; Schmatloch, Sabine; Hauke, Jan; Rey, Julia; Jackisch, Christian; Klare, Peter; Link, Theresa; Hanusch, Claus; Huober, Jens; Stefek, Andrea; Holtschmidt, Johannes; Schneeweiss, Andreas; et al. (Clinical cancer research, 2025)
The GeparOLA study evaluated paclitaxel plus olaparib (PO) in neoadjuvant chemotherapy for patients with HER2-negative early breast cancer with homologous recombination deficiency (HRD). HRD was defined by high HRD score or germline (g)/tumor (t) BRCA1/2 mutations (g/tBRCA1/2mut). In this study, we report long-term outcome data.GeparOLA (NCT02789332) was a randomized, multicenter, prospective, open-label, phase II trial. Patients with HER2-negative early breast cancer with HRD with an indication for chemotherapy (cT2-cT4a-d or cT1c and cN+ or cT1c and pNSLN+ or cT1c and triple-negative breast cancer, or cT1c and Ki-67 >20%) were randomly assigned to PO or paclitaxel + carboplatin (PCb), both followed by epirubicin + cyclophosphamide. Long-term efficacy endpoints were secondary endpoints and included invasive disease-free survival (iDFS), distant disease-free survival (DDFS), and overall survival, with a planned median follow-up of >4 years.Between September 2016 and July 2018, 107 patients were randomized and 106 (PO N = 69 and PCb N = 37) started treatment. The median age was 47.0 years; of all patients, 35.8% had cT1 tumors, 31.4% were cN+, 86.8% had G3 tumors, 89.6% had Ki-67 >20%, and 72.6% were triple negative. After a median follow-up of 49.8 months, 18 (15 in PO and three in PCb) iDFS events and seven (six in PO and one in PCb) deaths were reported. The 4-year iDFS (76.0% PO vs. 88.5% PCb, hazard ratio = 2.86; 95% CI, 0.83-9.90; log-rank P = 0.081), DDFS (81.2% PO vs. 93.4% PCb, hazard ratio = 3.03; 95% CI, 0.67-13.67; log-rank P = 0.129), and overall survival (89.2% PO vs. 96.9% PCb, hazard ratio = 3.27; 95% CI, 0.39-27.20; log-rank P = 0.244) tended to be inferior with olaparib. Patients without g/tBRCA1/2mut benefited from Cb (seven of 30 patients had iDFS/DDFS events in PO vs. 0/16 in PCb; log-rank P = 0.037), whereas no difference for patients with g/tBRCA1/2mut was observed (hazard ratio = 1.16, log-rank P = 0.83).For HER2-negative early breast cancer with HRD, olaparib showed a tendency for inferior outcomes compared with Cb, particularly in patients without g/tBRCA1/2mut. In patients with g/tBRCA1/2mut, olaparib may replace Cb.
Gesehen am 19.11.2025